Rejuvenation of the Midface - Freeman, M. Sean (Facial Plastic Surgery, 2018)
In this article, the interested reader will learn when and how to apply different techniques on their patients, with the goal of safe, effective, natural looking, and long-lasting midface rejuvenation.
Keywords: midface lift; midface aging; facial rejuvenation